RESTORASI LANSKAP SITU PENGARENGAN DEPOK UNTUK MENDUKUNG EKOSISTEM PERAIRAN BERKELANJUTAN - Hendrawan, Diana Irvindiaty; Qurrotu ‘Aini Besila; Ina Krisantia; Nadira Nur Shadrina (Jurnal Lingkungan dan Kota, 2023)
Situ (Shallow lake) Pengarengan with an area of 7 Ha serves as a water catchment area, flood control and conservation area. This study aims to analyze the damage that occurred in Situ Pengarengan and provide alternative solutions through landscape restoration technology. The main pollutants that enter the waters of Situ Pengarengan come from households, wastewater and garbage carried by the Kali Hati stream. Not all areas of Situ Pengarengan have adequate boundaries. Only 30% of the area has borders. Only 38% of the area has green open space. There are 17 types of plants on the banks of Situ Pengarengan. Situ landscape restoration technology is needed as an effort to improve ecosystem balance, restore ecological functions and increase the natural purification ability of situ water. One of the landscape restoration technologies by arranging landscapes uses plants that are able to hold runoff water to prevent erosion and as a natural filter for pollutants. Efforts to control damage and prevent pollution are carried out through the implementation of green open space according to the provisions, the implementation of communal Wastewater Treatment Plants (WWTP), the installation of garbage retention nets and periodic cleaning and dredging of situ. Landscape restoration is carried out for damage control through the preservation of catchment areas and reforestation of the boundaries.